The Effect Of Starting Juice On Reducing Blood Pressure In Hypertension Patients - Yunita Sri Hardiyanti; Ida Rosidawati; Yuyun Sholihatin; Asep Muksin (HealthCare Nursing Journal, 2023)
Hypertension is a silent killer disease because it can cause death, so proper treatment is needed. One of them is giving star fruit juice. Star fruit juice contains fiber, provitamin A, vitamin C, vitamin B1, vitamin B2, phosphorus, calcium, iron, and potassium and has analgesic, antihypertensive and diuretic properties that are beneficial for lowering blood pressure. The purpose of this study was to determine the effect of giving star fruit juice on reducing blood pressure in hypertensive patients in the work area of Tamansari Health Center. This research method uses a quasi-experimental with one group pretest-posttest design, the sample in this study was 18 people with a purposive sampling method. Analysis of the data using the dependent t-test. The results showed that the average blood pressure before was 154.89/95.83 mmHg and the blood pressure after was 137.72/85.78 mmHg. The results of the paired t-test for systolic blood pressure p value = 0.000 and diastolic blood pressure p value = 0.000 (p 0.05), then the hypothesis is accepted. The conclusion from the results of this study is that it is believed that there is an effect of giving star fruit juice to decrease systolic and diastolic blood pressure in hypertensive patients in the working area of Tamansari Health Center. It is recommended that hypertension patients consume star fruit juice, which is a complementary therapy in lowering blood pressure because the content in star fruit is very beneficial for the health of the body.